Kripke's Critique of Descriptivism Revisited - Baumann, Pierre (Princípios: Revista de Filosofia (UFRN), 2010)
Abstract: This paper has two purposes: the first is to critically examine Kripke’s well-known arguments against Descriptivism and suggest that they are not as decisive as many have thought; the second is to argue that proper names do encode descriptive information of various kinds, that such information may be truth-conditionally significant, and hence that a name’s truth-conditional contribution is not limited to its referent. Keywords: Kripke. Proper name. Scope. Modality